2000
DOI: 10.1073/pnas.97.26.14449
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection and speciation in field crickets

Abstract: Recent theoretical work has shown that sexual selection may cause speciation under a much wider range of conditions than previously supposed. There are, however, no empirical studies capable of simultaneously evaluating several key predictions that contrast this with other speciation models. We present data on male pulse rates and female phonotactic responses to pulse rates for the field cricket Gryllus texensis; pulse rate is the key feature distinguishing G. texensis from its cryptic sister species G. rubens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
149
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(159 citation statements)
references
References 71 publications
6
149
0
4
Order By: Relevance
“…Coyne & Orr 1989Seehausen et al 1997;Masta & Maddison 2002), and some have also demonstrated female preferences for local male signals (e.g. Seehausen et al 1997;Gray & Cade 2000). Divergence in male signals has proceeded faster than expected by genetic drift in Habronattus jumping spiders (Masta & Maddison 2002), but in this case, females do not prefer local male signals (Hebets & Maddison 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coyne & Orr 1989Seehausen et al 1997;Masta & Maddison 2002), and some have also demonstrated female preferences for local male signals (e.g. Seehausen et al 1997;Gray & Cade 2000). Divergence in male signals has proceeded faster than expected by genetic drift in Habronattus jumping spiders (Masta & Maddison 2002), but in this case, females do not prefer local male signals (Hebets & Maddison 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies provide tantalizing evidence that sexual selection may cause speciation in the wild (Coyne & Orr 1989Barraclough et al 1995;Seehausen et al 1997;Gray & Cade 2000;Masta & Maddison 2002), yet support for this hypothesis remains incomplete. To demonstrate conclusively that sexual selection drives speciation, several criteria must be met: male signals must differ significantly among populations or recent sister species; females must prefer local male signals to foreign ones; divergence in male signals must result from selection and not genetic drift; and finally, divergent signals and preferences must be correlated with restricted gene flow at nuclear loci to show that populations are diverging towards distinct species (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vamosi & Schluter 1999;Gray & Cade 2000;Bridle et al 2006), but the relative importance of sexual selection for postzygotic isolation is rarely investigated, due to it being a rather complicated undertaking. The most informative approach for estimating effects of hybridization is to measure the relative difference in fitness between hybrid and parental species under natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In many organisms, reproductive isolation often starts with individuals from distinct populations failing to recognize each other as potential mates (i.e., species recognition; Baker and Baker 1990;Gray and Cade 2000;Shaw and Parsons 2002;Patten et al 2004;Seehausen et al 2008). Such discrimination between incipient species is typically mediated by divergent mating signals, including visual (Baker 1991;Seehausen et al 2008), acoustic (Irwin et al 2001;Grant 2002a, 2002b), and olfactory (Mullen et al 2007) signals.…”
Section: Introductionmentioning
confidence: 99%